Alternativa de solución al deficiente funcionamiento de la planta de tratamiento de aguas residuales La Conaca en Pasaje - Chuchuca Zari, Miguel Ángel (My University, 2021)
The present study was carried out in the wastewater treatment plant of the La Conaca sector, Simón Bolívar parish of the Pasaje canton, El Oro province in lot # 1 of the Rio Norte Social Interest urbanization, whose general objective is to analyze environmental management in the wastewater treatment plant of the Conaca sector in the canton of El Oro province, guaranteeing the rights of nature. Through the bibliographic information obtained and research carried out in situ in the study area, some problems were found around the wastewater treatment plant, one of them; pollution in the sewer network, dumping of solid waste and lack of environmental awareness. Against this, unpleasant odors are produced and vectors are increased. As for other services such as the sewerage system, it is working correctly. What is intended to be verified in the investigation is that the treatment plant complies with current environmental regulations such as the Unified Text of Secondary Environmental Legislation, complies with the range of maximum permissible limit of physical, chemical and biological parameters. Whose purpose is that the final product is free of contamination, to avoid damage to the environment and human health. To describe the type of treatment carried out within the treatment plant, the person in charge of the area had to be interviewed, who tells us that they use an anaerobic system, this being the most economically accessible but not modern, but has a capacity of 152 m3 and a flow rate of 20 liters per second, collecting the sewage from the eight sectors.
El presente estudio se realizó en la PTAR la CONACA, del cantón pasaje, provincia de El Oro, cuyo objetivo general es analizar la gestión ambiental en la planta de tratamiento de aguas residuales del sector CONACA en el cantón pasaje, garantizando los derechos de la naturaleza. A través de la información bibliográfica obtenida e investigación realizada in situ en la zona de estudio, se encontraron algunos problemas alrededor de la planta de tratamiento de Agua residual, uno de ellos; contaminación en la red de alcantarillado, arrojamiento de residuos sólidos y falta de conciencia ambiental. Frente a esto, se producen olores desagradables y se incrementan vectores. En cuanto a otros servicios como el sistema de red de alcantarillado se encuentra funcionando correctamente. Lo que se pretende constatar en la investigación, es que la planta de tratamiento cumpla con las normas ambientales vigente como es el Texto Unificado de Legislación Secundaria del Medio Ambiente, cumpla con el rango de Límite máximo permisible de los parámetros físicos, químicos y biológicos. Cuyo propósito es que el producto final sea libre de contaminación, evite daños al medio ambiente y salud humana. Para describir el tipo de tratamiento que realizan dentro de la planta de tratamiento se tuvo que entrevistar al encargado del área, quien nos manifiesta que utilizan un sistema anaeróbico, siendo este el más accesible económicamente más no moderno, pero cuenta con una capacidad de 152 m3 y un caudal de 20 litros por segundos, recogiendo las aguas negras de los ocho sectores.
Keywords: GESTION AMBIENTAL; AGUA RESIDUAL; NORMA VIGENTE; SISTEMA ANAEROBICO